2023
DOI: 10.1093/lambio/ovac076
|View full text |Cite
|
Sign up to set email alerts
|

The function of the gene loiP in transformation efficiency and outer membrane permeability change of Escherichia coli treated by Ca2+ ions

Abstract: The preparation of Escherichia coli competent cells by calcium chloride is a common method in molecular biology, but the mechanism is poorly understood. In a previous study, using transcriptomics and proteomics approaches, we found that the expression pattern of the gene loiP was upregulated by CaCl2. In order to investigate the function of the loiP gene in Ca2+ mediated formation of competent cells of E. coli DH5α, the loiP gene deletion strains were constructed by the lambda-derived Red homologous recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Zhang et al obtained a key gene, bhsA, through transcriptome and proteome analysis and experimentally verified its involvement in Ca 2+ response [14]. Wan et al found that the loiP gene also has an influence on the development of the E. coli competent cells, as demonstrated through an extensive multiomics investigation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al obtained a key gene, bhsA, through transcriptome and proteome analysis and experimentally verified its involvement in Ca 2+ response [14]. Wan et al found that the loiP gene also has an influence on the development of the E. coli competent cells, as demonstrated through an extensive multiomics investigation [15].…”
Section: Introductionmentioning
confidence: 99%